Refinement of the locus for X-linked recessive chondrodysplasia punctata - Muroya, Koji; Ogata, Tsutomu; Rappold, Gudrun; Klink, Albrecht; Nakahori, Yutaka; Fukushima, Yoshimitsu; Aizu, Katsuya; Matsuo, Nobutake (Human genetics, 1995)
Although the locus for X-linked recessive chondrodysplasia punctata (CDPX1) has been mapped to the region between PABX and DXS31 (the critical region is about 3 Mb long), the precise location within the critical region has not been determined. In this paper, we describe a boy with a 46,Y,der(X)t(X;Y)(p22.3;q11)mat karyotype and review the genotype-phenotype correlations in three male patients with the combination of apparent lack of clinical features of CDPX1 and a partial deletion of the critical region. The results suggest that the region defined by the two BssHII sites at 3180 and 3570 kb from the Xp telomere may be the target region for the CDPX1 locus.
Gesehen am 30.03.2021